Augmented Reality Learning Media Development to Enhance Student Learning Motivation: A Systematic Literature Review - Naufa Daffa Anwar; Nala Aulatul Zahra; Nailul Inayah; Muhammad Aditya Saputra; Bakti Fatwa Anbiya (South Sulawesi Education Development (SSED), 2026)
This study aims to analyse the development of Augmented Reality (AR)-based learning media to increase students’ motivation to learn using the Systematic Literature Review (SLR) approach. The study was conducted by selecting articles from various databases using inclusion criteria related to the form of AR implementation, the effectiveness of AR in learning, and supporting factors and barriers to its use. The results of the review show that AR media is developed in various forms, such as marker-based, markerless, interactive modules, and 3D books. Consistently, AR has been shown to increase student motivation, attention, and engagement in learning through 3D visualisation and real-time interaction. However, device limitations, the need for stable internet connections, and teachers’ ability to operate technology are the main challenges to its implementation. These findings confirm that AR has the potential to be an effective, innovative learning medium, noting the need for facility adjustments, teacher training, and more systematic curriculum integration.